Is it time to revisit the role of ultrasound in rheumatoid arthritis management?. Issue 1 (9th November 2016) - D'Agostino, MA; Boers, M; Wakefield, R J; Emery, P; Conaghan, P G
Abstract : For over a decade, a large number of studies have highlighted the benefits of ultrasound (US) in the diagnosis and management of rheumatic diseases, especially rheumatoid arthritis (RA). However, its benefits in routine practice have been less studied and trials examining US as part of various clinical strategies are just emerging, with recent randomised trials examining the added value of US in tight-control paradigms. The conclusions of these trials have raised questions on the role of US in RA management. This Viewpoint analyses the recent studies, and discusses potential limitations in study designs as well as the methodological challenges of assessing the added value of an imaging technique.